Botulinum toxin as a double‐edged sword in alopecia: A systematic review. (17th August 2020) - Wang, Yuanzhuo; Zhang, Hanlin; Zheng, Qingyue; Tang, Keyun; Fang, Rouyu; Sun, Qiuning
Abstract: Background: Alopecia is a common disease influencing the quality of life of the patients. Botulinum toxin has been widely employed in cosmetic dermatology and was applied in some clinical trials to treat alopecia. Aims: Hence, We conducted a systematic review to examine the safety and efficacy of using botulinum toxin in treating alopecia. Methods: Cochrane Library, Embase, PubMed, and Web of Science databases were used to search for articles. A PICOS question was formed and the author, year of publication, number of participants, study design, product, dilution and dosing, outcome measurement, findings, side effects, and follow‐up were retrieved. The Oxford Centre for Evidence‐Based Medicine 2011 Levels of Evidence was used as a qualitative indicator to evaluate the levels of evidence. Results: Eleven articles published between 2005 and 2019 were included. 9 of which were about treatment effects and 2 were concerning adverse effects. The total number of the participants was 106, and the number for each article was ranged from 1 to 50. Varying type of outcome measurements was used for the publications. 8 articles were evaluated as Level 4 and 1 was evaluated as Level 5 during the 9 articles with treatment effects. Conclusions: The results showed that botulinum toxin may function as a double‐edged sword and have a low degree of efficacy and safety in treating alopecia. The study may be useful to remind the physicians of adverse effects in clinical practice and pave the way for further research. A larger, randomized, placebo‐controlled study is warranted.